Improving Students’ Academic Achievement in 2nd Year Horticulture Students - Yohannes, Belayneh (International Journal of Educational Research & Social Sciences, 2022)
Peer learning is underpinned by social constructivist learning theory. Collaborative peer learning is a means of preparing learners to become independent and actively involved in constructing knowledge for themselves and understanding how to use it. The objectives of The study was to distinguish the major problems that affect the implementation of peer learning in the department and to find and apply possible strategies that help to improve student’s academic this study was achievement used two stage sampling. Methods in the first stage 2nd year horticulture students were selected, and then random sampling method was applied. The study identified that, unequal sharing of tasks among group members, Problem of group organization/formation, lack of students’ a preparation were the major problems